The Role of English Theater Performing Arts in Improving Children's Language Fluency and Communication Skills at School - Annisa, Rossy; Ismahani, Siti (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Abstract : This qualitative case study investigates how performing arts, namely English theater, can improve children's language proficiency and communication skills in an educational context. 37 individuals participated in the study as research respondents, using a qualitative technique. The findings show that theater arts significantly improve pupils' linguistic skills. Students gain enhanced language skills and confidence in their ability to express themselves and communicate with others via immersive theatrical activities. This study emphasizes how important it is to incorporate performing arts into school curricula in order to support pupils' overall language development. Keyword: English theatre, performing arts, communication skills, teaching English